EDUKASI PENANGANAN AWAL GIGITAN ULAR DI DESA KEDUNGSALAM DAN BANJAREJO KECAMATAN DONOMULYO KABUPATEN MALANG - Putra, Exgha Dwi; Prasetyadjati, Ari; Zaiyanah, Munsifah; Hevy, Nuretha; Mustafa, Ahmadal; Fitriyani, Insan; Kinanda, Erka Wahyu; Lian, Johnatan De; Analisa, Sabrina (Jurnal Abdi Insani, 2025)
Snake bites are classified as a "Neglected Tropical Disease" by the WHO, with over 100,000 deaths occurring annually worldwide, primarily in densely populated developing countries, including Indonesia. Farmers are the most vulnerable group to snake bites, especially during the rainy season and when agricultural activities increase. In implementing programs to control incidents, several factors are needed, including the necessity for educational programs to enhance public understanding of the dangers of snake bites and preventive measures. Donomulyo is a district in Malang Regency, East Java Province, Indonesia. Donomulyo is located in the southwest part of Malang Regency, with the majority of its population working as seasonal farmers who cultivate various commodities such as rice, sugarcane, corn, and coconuts. The methods used in this activity include outreach, pre-tests and post-tests, educational videos, and practical sessions. After these activities, an evaluation will be conducted comparing pre-test and post-test scores, followed by normality tests and difference tests using the Wilcoxon test.The results showed that there were 46 participants, consisting of 44 males and 2 females, where most participants were farmers—a profession with a high risk of snake bites. From the normality test results, it was found that the data were not normally distributed; therefore, the Wilcoxon test was used. The results indicated a significant difference between pre-test and post-test scores with a value of 0.002 (<0.005).